RECYCLING OF TEXTILE WASTE INTO SOUND-ABSORBING ACOUSTIC PLATES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The textile waste problem is a significant concern both in Latvia and globally. The textile industry, particularly the fashion industry, is considered one of the most polluting industries, generating a substantial amount of waste. Worldwide, the production of textiles has been on the rise due to population growth and increased consumption, leading to a significant increase in textile waste generation. The management of textile waste is crucial for ensuring sustainability and minimizing environmental impacts. Recycling and reusing textile waste are essential strategies for implementing a circular economy model and reducing the environmental hazards associated with textile production and disposal. One way we can reduce the amount of textile waste in landfills is to create new products from this waste by intercepting it before it ends up in landfills. The aim of this study is to develop sound-absorbing acoustic plates using textile waste. Experiments with textile waste started in January 2024, beginning with the acquisition of textile waste. The textile obtained for the experiment was sourced from the waste management company in Latvia's North Vidzeme, which collects clean textile waste from residents. In the next stages, textile waste was shredded, and slabs were formed using a compactor. Textile processing into a finer fraction was carried out using an industrial shredding machine. A mixture of water-based glue, an isotonic solution (containing boric acid and sodium borate), PVA glue, and sodium bicarbonate was used as a binder for making the plates. The created plates were tested for acoustic properties in the laboratory. The absorption coefficient of the acoustic plate at the best performance level (1250 - 3500 Hz) ranged from 1.14 to 1.6. This is consistent with the fact that non-separated textiles were used.